Design of An Interactive Module for Historical Building Learning Using Board Game Puzzle Based On Multi-Marker Augmented Reality - Pujo Prasetyo aji; Herman Tolle; Eko Sakti Pramukantoro (JITeCS (Journal of Information Technology and Computer Science), 2023)
Augmented Reality (AR) technology is one of the new technologies that can display the virtual world into the real word. Augmented reality technology is widely applied into the educational field to help the learning process by representating an object in more realistic and detailed way. However, most of the implementations that carried out only using AR to show up an object from a single marker, even though there are still many ways on using AR functions to represent an information in more detailed and intersting ways.